A Brief Compass for the Deployment of Artificial Intelligence Systems by Public Administrations, with Fundamental Rights as the Guiding North - Carlón Ruiz, Matilde (2025)
Public administrations cannot ignore the numerous opportunities offered by artificial intelligence tools, given their variety and versatility. These opportunities are not, however, without risk, particularly with regard to the protection of fundamental rights. The Artificial Intelligence Regulation adopted by the European Union in June 2024 acknowledges this, requiring public authorities deploying high risk AI systems to carry out an impact assessment. This assessment offers a valuable tool for public administrations to weigh the very decision of whether or not to implement the system.